Rancang Bangun Sistem Informasi Pengukuran Indikator Utama Kegiatan Perguruan Tinggi Politeknik Negeri Pontianak - Suharto, Irawan; Ramli, Ramli; Adam, Safri; Noor, Diah Laksmini; Gautama, Boy; sino, sino (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2024)
Universities are providers of higher education that provide advanced education from secondary level to formal education. To carry out educational activities, universities need a set of organizational structures so that educational activities run well. Every quarter, all departments and work units are required to report their achievements based on the main performance indicators of higher education. The method used to report key performance indicators is by filling in the data in the Microsoft Excel application which has been created previously in template form. This becomes a problem when measuring performance in the following quarter, each department and work unit must copy the previous quarter's file and enter the same data plus new data. This becomes a problem when synchronizing data in Excel and in Google Drive. Sometimes the departments or work units that input data and supporting evidence are not careful so that the achievement data written in Excel is different from the supporting evidence that is uploaded. Another problem that arises is the limited Google Drive offline storage capacity, which is only 15 GB per account, while the supporting evidence uploaded may be more than that. Based on the problems above, this research proposes a solution by designing and building a web-based information system that is used to input data and measure the performance of higher education activities. This system was built using the waterfall software development method, using the Laravel framework based on the PHP programming language. The database in this system will use My SQL DBMS (Database Management System). The result of this research is a prototype of a web-based primary performance measurement application that can be used as a system for uploading IKU data which is then captured and calculated for its achievements. Keywords :, Database, Information System, Electronics